The Effect of Blood Flow Restriction Training on Ankle Sprain Repair: A Narrative Review - Bagheri, Azadeh; Roostayi, Mohammad Mohsen; Hosseini , Seyed Majid; Roostaei , Hanieh (Journal of Clinical Physiotherapy Research, 2023)
Introduction: Ankle Sprain (AS) is one of the most common musculoskeletal injuries in athletes. Without proper intervention, acute AS have a high recurrence rate, which is associated with the development of chronic ankle instability. Currently Limited evidence exists to support the best intervention in related to individuals with AS. Blood Flow Restriction Training (BFRT) has emerged as a promising approach in physiotherapy for individuals with AS. The aim of present study was to review the effectiveness of BFRT treatment in individuals with AS narratively. Materials and Methods: This narrative review was conducted to reviewing the available research’s about the role of BFRT in treatment of individuals with AS. The search encompassed studies published from 2000 to 2024 across multiple electronic databases, including Google Scholar, PubMed, Scopus, and Science Direct using relevant keywords. Results: Evidence suggests that the BFRT can be used as a new method in the treatment and rehabilitation process of individuals with AS. Conclusion: Research has shown that utilizing BFRT can lead to significant improvements in recovery rates, strength gains, and overall patient satisfaction.